Xenogeneic human p53 DNA vaccination by electroporation breaks immune tolerance to control murine tumors expressing mouse p53. - Ruey-Shyang Soong; Janson Trieu; Sung Yong Lee; Liangmei He; Ya-Chea Tsai; T-C Wu; Chien-Fu Hung (PLoS ONE, 2013)
The pivotal role of p53 as a tumor suppressor protein is illustrated by the fact that this protein is found mutated in more than 50% of human cancers. In most cases, mutations in p53 greatly increase the otherwise short half-life of this protein in normal tissue and cause it to accumulate in the cytoplasm of tumors. The overexpression of mutated p53 in tumor cells makes p53 a potentially desirable target for the development of cancer immunotherapy. However, p53 protein represents an endogenous tumor-associated antigen (TAA). Immunization against a self-antigen is challenging because an antigen-specific immune response likely generates only low affinity antigen-specific CD8(+) T-cells. This represents a bottleneck of tumor immunotherapy when targeting endogenous TAAs expressed by tumors. The objective of the current study is to develop a safe cancer immunotherapy using a naked DNA vaccine. The vaccine employs a xenogeneic p53 gene to break immune tolerance resulting in a potent therapeutic antitumor effect against tumors expressing mutated p53. Our study assessed the therapeutic antitumor effect after immunization with DNA encoding human p53 (hp53) or mouse p53 (mp53). Mice immunized with xenogeneic full length hp53 DNA plasmid intramuscularly followed by electroporation were protected against challenge with murine colon cancer MC38 while those immunized with mp53 DNA were not. In a therapeutic model, established MC38 tumors were also well controlled by treatment with hp53 DNA therapy in tumor bearing mice compared to mp53 DNA. Mice vaccinated with hp53 DNA plasmid also exhibited an increase in mp53-specific CD8(+) T-cell precursors compared to vaccination with mp53 DNA. Antibody depletion experiments also demonstrated that CD8(+) T-cells play crucial roles in the antitumor effects. This study showed intramuscular vaccination with xenogeneic p53 DNA vaccine followed by electroporation is capable of inducing potent antitumor effects against tumors expressing mutated p53 through CD8(+) T cells.